Fundamentals of Entrepreneurship (ENT300) : Business Plan on Ice Dream / Ann Fernah Donnie … [et al.] - Ann Fernah, Donnie; Dadie, Feliscia; Daang, Avyline Augustine; Kelvin, Khimarion; Sia, Dorthy Venson (2018)
Ice Dream offer a various flavor of ice cream and also we are providing a snack and beverage to the costumer. Our main product is ice cream. We provides cone ice cream, and cup ice cream with three different size which is small, medium and large. Ice Dream provides many flavor of ice cream where the costumer can choose their own favorite ice cream and mix it to three flavor in one cup or cone. This can make the costumer satisfied where they can taste three flavor of ice cream instead the have to buy different flavor in other cup. It is also can save the costumer's money.